Biodiversity of Phytoplankton in Two Aquatic Ecosystems (LOTIC and LENTIC) During the Autumn Season - Hind Mahdi Salih Al-Saeedi, Ibrahim M. A. Al-Salman (Pakistan Journal of Medical & Health Sciences, 2022)
Phytoplankton have been studied in quantity and quality in two aquatic ecosystems represented by two sites in the lake of Baghdad Island tourist as a lotic ecosystem and two sites of the Tigris River, one north of the lake and the other south as an lentic ecosystem, and the study was conducted in the autumn of 2021, where 69 species were diagnosed in the environment of the two ecosystems studied, distributed to 14 species of Chlorophyta, 21 species of Cyanobacteria, 29 species of diatom (1 belongs to Centrales order and 28 to Pennales order), 3 species of Euglenophyta and two species of the Chrysophyta division. The dominance of algae belonging to the genus of; Pinnularia, Synedra, Ankistrodesmus, Chroococcus, Oscillatoria, Synechacoccns, Navicula and Nitzschia during the autumn period and at all Sites. Some species showed high density such as: Ankistrodesmus falcatus, Chroococcus disperses, Chroococcus minor, Oscillatoria limnetica, Synechacoccns aeruginosus, Navicula sp. and Nitzschia longissima. The quantitative results showed that the mean density of the phytoplankton in the lotic aquatic ecosystem exceeded that the lentic aquatic ecosystem when recorded (378.68 × 103 cells/L and 334.21×103 cells/L) respectively. Air temperature values were recorded (20-36) °C and while water temperature ranged between (16-25.5) °C, NTU (5.8-19.5) 4), TDS (421-620) mg/L, as well as EC (1027-1380) μS/cm, whereas pH value was (7.4-8.4), (DO) (6.4-8.6), and BOD (204-305). Also, by measuring the values of the essential macronutrients for algae growth, it was found that the values of concentrations NO3 (0.468-0.986), PO4- (0.038-0.061) SO4- (175.6-293.37), and SO3 (3.9-6.9) mg/L respectively.